The influence of moral norm toward organic food purchase intention among Malaysian consumers: A conceptual study - Mohamad, Mohamad Amiruddin; Mat Issa, Zuraini; Abdul Latip, Muhammad Safuan (International Journal of Accounting, Finance and Business, 2025)
The production of organic food that adheres to sustainable practices has been acknowledged for its contribution to environmental protection. This suggests that consumers' purchase decisions on organic food can be motivated by both health benefits and a sense of responsibility to protect the environment. However, the growth of organic food in Malaysia remains a niche product, despite its known beneficial characteristics. Recognising this situation, this study has utilised the Theory of Planned Behaviour (TPB) to develop a conceptual framework for examining the factors that influence Malaysian consumers' purchase intentions regarding organic food. While the TPB consists of three main predictors, this study proposes an extension by integrating a moral norm into the framework that emphasises ethical consideration. This approach is relevant within the context of organic food as it supports environmental sustainability. As such, this highlights the need for further investigation into how moral norm can shape consumers' purchase intentions toward organic food, considering that the organic food market in Malaysia is still developing and is consumed by a relatively small population. To address this, the study proposed a quantitative approach for data collection through a structured questionnaire. SPSS and SmartPLS 4 will be used in this study to analyse descriptive statistics and inferential statistics. By integrating moral norm into the TPB, the study aims to offer insights into consumer behaviour toward sustainable consumption. The findings are anticipated to contribute to both academic and practical perspectives, highlighting the aspect of moral norm and their influence on consumers' purchase intention toward organic food in Malaysia.